2022
DOI: 10.3168/jds.2021-20420
|View full text |Cite
|
Sign up to set email alerts
|

Bovine colostrum: Postpartum changes in fat globule size distribution and fatty acid profile

Abstract: Although "zero waste" valorization concepts are gaining increasing attention, colostrum, a byproduct of milk production, remains underused due to technological challenges. Information about the fat fraction and the size of fat globules is needed to address these challenges, but such information is currently lacking. This study aimed to fill this gap in the knowledge by measuring the size distribution of bovine colostrum fat globules (CFG) and analyzing its relationships with postpartum milkings, parity, and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…Sats et al . (2022) reported similar proportions of ω‐3 and ω‐6 in colostrum to those reported here (1.19 and 2.6 g/100 g FA respectively).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Sats et al . (2022) reported similar proportions of ω‐3 and ω‐6 in colostrum to those reported here (1.19 and 2.6 g/100 g FA respectively).…”
Section: Discussionsupporting
confidence: 85%
“…Given the anti-inflammatory functions of DPA derivatives (Groeger et al 2010;Cipollina et al 2014), high proportions in colostrum and transition milks may have significant benefits in calf neural development (Helland et al 2003). Sats et al (2022) reported similar proportions of x-3 and x-6 in colostrum to those reported here (1.19 and 2.6 g/100 g FA respectively).…”
Section: Discussionsupporting
confidence: 70%
“…Although these PLS models have been created to analyze milk across most of a lactation, they were not designed to analyze constituents during the transition from colostrum to milk. Research by Sats et al (2022) indicated that the fourth milking of a postpartum cow is colostrum transition milk, and all prior milkings are colostrum. Because the study farm milked 3 times a day, a cow could still be producing transition milk on 2 DIM, depending on when she calved.…”
Section: Discussionmentioning
confidence: 99%
“…The electrostatic charge that the particles carry is essential for the stability of the milk emulsion. Monitoring the particle size is crucial to ensure milk satisfies consumer demands, legal requirements, and shelf-life regulations [ 109 ].…”
Section: Dls and Its Applicationsmentioning
confidence: 99%